リュツォ・ホルム ワン エンガンイキ ノ ヒョウメン オンド ブンプ - 中川, 清隆; ナカガワ, キヨタカ; Nakagawa, Kiyotaka (1997)
P(論文) 1990年2月-1991年1月に昭和基地で受信された全NOAA/AVHRR熱赤外画像が解析され, 温度分布図が作成された。この解析の結果, リュツォ・ホルム湾沿岸, 特に宗谷海岸の氷床斜面中腹に高温域, いわゆる斜面温暖帯が, 冬季頻繁に出現した。宗谷海岸の斜面温暖帯と昭和基地の接地逆転層の関係が調査された。接地逆転層の厚さが増すに従って, 斜面温暖帯は氷床斜面の内陸側, 高所側に変位した。しかしながら, 昭和基地に接地逆転層が出現しても, 斜面温暖帯は必ずしも出現しなかった。氷床斜面に斜面温暖帯が出現するか否かは氷床上の接地逆転層, すなわち, カタバ風が, 氷床斜面末端の接地逆転層とどの様に関わっているかによると考えられる。 All the NOAA/AVHRR thermal infrared images received at Syowa Station from February 1990 to January 1991 were analyzed to make temperature distribution maps. From this analysis the warmer area in midslope, i. e. the so-called thermal belt (D. GREENLAND, The Encyclopedia of Climatology, ed. by OLIVER and FAIRBRIDGE, 594,1987), appeared on the ice sheet slope along the coast around Lutzow-Holm Bay, especially on the Soya Coast, frequently in winter. The relationship between the thermal belt on the Soya Coast and the surface inversion layer over Syowa Station was investigated. When the surface inversion layer thickness increased, the thermal belt was displaced toward the interior or higher part of the ice sheet slope. However, even if the surface inversion layer appeared over Syowa Station, the thermal belt did not necessarily appear. The appearance or absence of the thermal belt on the ice sheet slope is considered to correspond to how the surface inversion layer over the ice sheet, a katabatic wind, connects with the surface inversion layer over the foot of the slope. departmental bulletin paper